Efeitos de spin em diodos de tunelamento ressonante não-magnéticos tipo-n - Santos, Lara Fernandes dos (Universidade Federal de São Carlos, 2007)
In this work, we have investigated spin polarization effects in asymmetric ntype resonant tunneling diodes (RTDs). When subjected to an external magnetic field parallel to the tunnel current, the Zeeman effect leads to the spin splitting of confined levels in the structure. The spin-dependent carrier injection on the asymmetric diode was investigated by measuring the left-and right-circularly polarized light emission intensities from the quantum well (QW) and contact layers as a function of the applied voltage. Under illumination, we observed distinct peaks in the current-voltage characteristics associated to the resonant tunneling of photoinduced holes and electrons through confined levels in the QW. The optical polarization and the spin splitting of the QW emission present a strong dependence on both the laser excitation intensity and the applied bias voltage. Depending on the laser excitation conditions, we have observed a signal inversion of the circular polarization from the QW. We have also evidenced the formation of a spin polarized two dimensional electron gas in the ntype contact. The results show that non-magnetic n-type RTDs can be used as voltagecontrolled spin filters for the development of spintronic devices.
Keywords: Spintrônica; Fotoluminescência; Diodos; Tunelamento (Física); CIENCIAS EXATAS E DA TERRA::FISICA